2013
DOI: 10.1111/etp.12045
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the mechanical properties of nickel–titanium endodontic instruments

Abstract: Differences in mechanical properties between endodontic instruments might be related to the chemical composition, phase constitution, or fabrication process of nickel–titanium (NiTi) endodontic instruments. An awareness and knowledge of the mechanical properties of NiTi endodontic files and their association with the metallurgical properties is useful for clinicians to understand the behavior of NiTi instruments in root canals and help them to make decisions regarding which instruments are appropriate for root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 94 publications
2
105
0
6
Order By: Relevance
“…If the temperature is below martensite finish temperature ( M f ), the NiTi alloy is in martensitic state, that is, it is soft, ductile, can easily be deformed and possesses the shape memory effect (Zhou et al . ). Because of the reorientation capacity of the twinned phase structure, martensite has a superior cyclic fatigue resistance compared with austenite (Shen et al .…”
Section: Metallurgical and Mechanical Characteristics Of Niti Alloymentioning
confidence: 97%
See 1 more Smart Citation
“…If the temperature is below martensite finish temperature ( M f ), the NiTi alloy is in martensitic state, that is, it is soft, ductile, can easily be deformed and possesses the shape memory effect (Zhou et al . ). Because of the reorientation capacity of the twinned phase structure, martensite has a superior cyclic fatigue resistance compared with austenite (Shen et al .…”
Section: Metallurgical and Mechanical Characteristics Of Niti Alloymentioning
confidence: 97%
“…Concerning the phase constitution, other techniques such as XRD (X‐ray diffraction), metallographic examination and SEM (scanning electron microscopy) are needed to confirm the findings of the DSC analysis (Zhou et al . ).…”
Section: Metallurgical and Mechanical Characteristics Of Niti Alloymentioning
confidence: 97%
“…These instruments are manufactured from M-wire alloy that is claimed to improve file flexibility and resistance to cyclic fatigue whilst retaining cutting efficiency (Alapati et al 2009, Zhou et al 2013. It has an innovative off-centred rectangular cross section that gives the file a snake-like swaggering movement as it advances into the root canal.…”
Section: Introductionmentioning
confidence: 99%
“…They do not, however, display the conventional stress-induced martensitic transformation observed in conventional NiTi alloys. 41 A major weakness of martensitic instruments is their higher tendency for permanent plastic deformation during instrumentation. Peters et al 42 reported that 82% of CM instruments plastically deformed after instrumentation with smaller size instruments having a higher tendency to plastically deform for a given torque value, and other instruments not regaining their original shape after the sterilization procedure.…”
Section: Thermal Treatments Of Niti Alloysmentioning
confidence: 99%